Improving English Vocabulary and Writing Mastery with Audio Visual Media - Ridayani, Ridayani (English Education and Literature Journal (E-Jou), 2024)
This research was motivated by observations of students' English language skills. Seeing the phenomenon of students' abilities, it is felt necessary to be more intensive in improving their mastery apart from the learning material provided. This encourages educators to apply English audio-visual media to train students to get used to hearing English pronunciation. The aim of this research is to determine the importance of improving vocabulary mastery and English writing using audio-visual media. The approach used in this research is qualitative with descriptive analysis. The sample in this research was a literature review of previous research on published books, newspapers and scientific articles. Samples were taken in the form of articles about English vocabulary and writing using audio-visual media. Data collection techniques use test techniques to strengthen the influence of sampling and vocabulary. The results of the analysis indicate that efforts to increase vocabulary are followed by improving writing skills first. Therefore, the more vocabulary a student has from audio-visual media, the better he or she will be at writing English text content